Carbetocin Or Oxytocin To Prevent Postpartum Haemorrhage Due To Uterine Aony In Cases Of Elective Caesarean Section - Emarah, Mohamed S. A. (Advances in Social Sciences Research Journal, 2020)
Background: Despite the technological advancement made in the past few decades, postpartum haemorrhage (PPH) remains one of the principal causes of maternal deaths in developing nations. The administration of uterotonic drugs widely prevents the PPH; therefore, it is the main point of active management. Among uterotonics, oxytocin has proven to be very effective in reducing the incidence of PPH. One prophylactic drug which has been introduced in recent times is carbetocin, a synthetic long-acting oxytocin analogue. It has a longer half life of 41 min, allowing it to stimulate a prolonged uterine response of up to an hour after a single intravenous dose, obviating the need for infusion. Methods: A total of 120 pregnant women divided into two groups; Group I (Carbetocin group) included 60 women who received carbetocin and delivered by caesarean section (CS), Group II (Oxytocin group) included 60 women who received oxytocin and delivered by caesarean section (CS). Results: Our result showed that, there was a statistically significant difference for the prevention of atonic postpartum hemorrhage between the two groups (p<0.01), for carbetocin group. There was also a statistically significant difference between the two groups (p < 0.01), according to need to additional procedures, such as need to modified B-lynch sutures and need to bilateral uterine arteries ligation for carbetocin group. Conclusion: We concluded that carbetocin was a better alternative to traditional oxytocin in the prevention of PPH after elective caesarean section.